Absence of hydroxyurea‐induced mutational effects supports higher utilisation for the treatment of sickle cell anaemia. (11th February 2021) - Ware, Russell E.; Dertinger, Stephen D.
Summary: Hydroxyurea (hydroxycarbamide) is approved for treating both children and adults with sickle cell anaemia (SCA). Fetal haemoglobin (HbF) induction is the primary treatment response, along with improved anaemia, reduced haemolysis, myelosuppression and decreased endothelial inflammation. Hydroxyurea has proven clinical efficacy for SCA — treatment significantly reduces disease manifestations and prolongs survival. Despite these recognised benefits, long‐standing concerns regarding the risks of mutagenic and potentially carcinogenic drug exposure have hampered efforts for broad hydroxyurea use in SCA, although these are based largely on outdated experimental models and treatment experiences with myeloproliferative neoplasms. Consequently, many patients with SCA are not receiving this highly effective disease‐modifying therapy. In this review, we describe the concept of genotoxicity and its laboratory measurements, summarise hydroxyurea‐associated data from both preclinical and clinical studies, and discuss carcinogenic potential. The genotoxicity results clearly demonstrate that hydroxyurea does not directly bind DNA and is not mutagenic. Rather, its genotoxic effects are limited to indirect clastogenicity occurring in select cell types, and only when high dose and time thresholds are exceeded. This absence of mutagenic activity is consistent with the observed lack of any compelling carcinogenic potential. Since hydroxyurea therapy for SCA carries minimal carcinogenic risks, the current drug labelling should be modified accordingly, and prescribing practices should be broadened to allow better access and increased utilisation of this highly effective drug.